Use of sorghum-based distillers grains in diets for nursery and finishing pigs - Senne, B.W.; Mavromichalis, I.; Johnston, S.L.; Sorrell, P.S.; Kim, I.H.; Hines, Robert H.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments were conducted to etermine the effects of sorghum-based distillers dried grains with solubles in isocaloric diets for nursery and finishing pigs. Rate and efficiency of gain in nursery pigs were decreased with 45% or more distillers grains. For finishing pigs, efficiency of gain was improved as distillers grains was increased to 60% of the diet, and carcass fatness was increased by about .1 inch at the highest concentration.
Keywords: Swine; Distillers grains; Nursery pigs; Finishing; Sorghum